Gesetz zum Schutz gegen Fluglärm. - Ekardt, Felix; Heß, Franziska (Nomos, 2019)
Der gesetzliche Schutz vor Fluglärm wurzelt im Grundrecht auf Leben und Gesundheit. Wie meist bei mittel- und längerfristig wirkenden Gefährdungslagen ist die Sicherung eines adäquaten Schutzniveaus für die Betroffenen eine Aufgabe, die bislang nur schrittweise realisiert werden konnte. Das Thema ist zentral bedeutsam für Betroffene, Zulassungsbehörden, Flughafenbetreiber, die Anwaltschaft und die Gerichte. Der neue Handkommentar zum Fluglärmgesetz bietet erstmals Raum für eine kritische, an den Fragen der Genehmigungs- und Betreiberpraxis orientierte Gesamtdarstellung (FluglG, 1.-3. FluglSV, RL 2002/49/EG). Er bezieht den aktuellsten Stand der Regulierung auch auf Verordnungsebene ein.

After a long lead time the amended Act for Protection against Aircraft Noise came into force in June 2007. The act provides considerably larger noise protection areas at civil airports and military airfields. The determination of the noise protection area is based on the predicted air traffic at the airport. An innovation is the introduction of a supplementary factor in the distribution of aircraft movements for the different take-off or landing directions at the airport. This factor is three Sigma and describes the variation of the use of the individual runways in the past ten years. Further details are laid down in the drafts of the new Data Acquisition System (DES) and the new Calculation Instructions (AzB). These regulations were elaborated by an expert group under the chairmanship of the Federal Environment Agency. The DES was fundamentally revised and contains now also criteria for the quality assurance. The new AzB is based on the Document 29 (3rd edition) of the European Civil Aviation Conference (ECAC) and the DIN 45684-1. A segmentation technique is applied for the noise calculation with which the three-dimensional flight path of the aircraft is disassembled in linear segments. The AzB enables the determination of the equivalent sound pressure level for day and for night and as well as the Number Above Threshold (NAT) criterion. The calculation takes into account various factors, in particular aircraft noise emission data, the number of aircraft movements in the six busiest months of the prediction year as well as flight routes. In addition taxiing aircraft on the airport is taken into consideration in the necessary extent.
The determination of the noise protection area according to the Act for Protection against aircraft noise.
Keywords: Verkehr; Gesetz; Flugverkehr; Verkehrslärm; Lärmschutz; Gerichtsentscheidung